Harmony in Interfaith Marriage: A Phenomenological Perspective of Alfred Schutz in Bandungan District, Semarang Regency, Central Java - Muhammad Ulinnuha (Indonesian Association of Islamic Family Law Lecturers, 2024)
Problem statement: The main problem in this study is that interfaith marriage lies in the tension between individual freedom in choosing a life partner and the legal restrictions and religious norm that regulate the validity and sosial implications of the marriage. Objective: This study aims to capture, understand, and elucidate the meaning behind the phenomenon occurring within families practising interfaith marriage, wherein harmonious and tolerant relationships are established both within the family unit and in the broader community. Methods: This article employs a qualitative research methodology, specifically field research utilising a phenomenological approach. Data collection techniques encompass observation, in-depth interviews, and documentation. Results: The findings indicate that interfaith marriages in Dusun Kedungwangan demonstrate harmony both internally and externally. Internally, harmony is evidenced through communication patterns, educational dynamics, economic balance, and a low incidence of family-related issues. Externally, harmony is reflected in the establishment of harmonious interreligious social relationships within the community. The analysis, guided by Alfred Schutz’s phenomenological theory, identifies two key aspects in uncovering the meaning of social phenomena in the daily life of Dusun Kedungwangan: